The Rancang Bangun Prototipe Sistem Otomatis Bangunan Pintar Pada Rumah Kos Bertingkat: Rancang Bangun Prototipe Sistem Otomatis Bangunan Pintar Pada Rumah Kos Bertingkat - Darmawan, Muhammad Diky (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2023)
Abstract - Comfort in a room is able to provide relaxation for tired bodies from daily activities therefore using Smart Building Automatic System technology which can also be called a smart building is a design of construction and technology protection that is suitable for use to bring out all the functionality and comfort for residents with the aim of also reducing operational costs, and extending the life of the physical form. For the components that will be used, there is a connection through the local network that has been provided, so that it can be used for various things, one of which is used to monitor and monitor lighting control in a commercial building. This research will build a system using the Esp-32 which is used as a microcontroller, then to monitor temperature and humidity will use the Dht-11 sensor which is used to control the automatic blower system, and also use the LDR sensor module which is used as a light controller automatically and manually. , and all these results will be displayed on the Node Red dashboard which is the monitoring center. Because you could say that lighting is the largest source of energy used by humans, thus resulting in increased operational costs that must be incurred, especially if the use of this energy is not properly controlled. Keywords: Smart Building Automatic System, Esp 32, Node Red, Dht 11, LDR Sensor Module